2021
DOI: 10.1038/s41396-021-00945-7
|View full text |Cite|
|
Sign up to set email alerts
|

Non-antibiotic pharmaceuticals promote the transmission of multidrug resistance plasmids through intra- and intergenera conjugation

Abstract: Antibiotic resistance is a global threat to public health. The use of antibiotics at sub-inhibitory concentrations has been recognized as an important factor in disseminating antibiotic resistance via horizontal gene transfer. Although non-antibiotic, human-targeted pharmaceuticals are widely used by society (95% of the pharmaceuticals market), the potential contribution to the spread of antibiotic resistance is not clear. Here, we report that commonly consumed, non-antibiotic pharmaceuticals, including nonste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 87 publications
1
66
0
Order By: Relevance
“…This indicated that nonantibiotic pharmaceuticals could specifically elevate the plasmid uptake ability of such pathogenic microbes. Moreover, in addition to the above-mentioned relative abundance of transconjugant or recipient bacterial community under the exposure of non-antibiotic pharmaceuticals, the absolute number of donor bacteria was not significantly changed when challenged with these nonantibiotic pharmaceuticals [46]. This indicated bacterial community variation was due to the influence of external non-antibiotic pharmaceuticals, rather than bacterial number.…”
Section: Non-antibiotic Pharmaceuticals Affect the Transconjugant Mic...mentioning
confidence: 87%
See 1 more Smart Citation
“…This indicated that nonantibiotic pharmaceuticals could specifically elevate the plasmid uptake ability of such pathogenic microbes. Moreover, in addition to the above-mentioned relative abundance of transconjugant or recipient bacterial community under the exposure of non-antibiotic pharmaceuticals, the absolute number of donor bacteria was not significantly changed when challenged with these nonantibiotic pharmaceuticals [46]. This indicated bacterial community variation was due to the influence of external non-antibiotic pharmaceuticals, rather than bacterial number.…”
Section: Non-antibiotic Pharmaceuticals Affect the Transconjugant Mic...mentioning
confidence: 87%
“…It should be noted that the absolute number of donor bacteria was not significantly changed when challenged with these non-antibiotic pharmaceuticals [42]. This indicated bacterial community variation was due to the influence of external non-antibiotic pharmaceuticals, rather than bacterial number.…”
Section: Non-antibiotic Pharmaceuticals Affect the Transconjugant Mic...mentioning
confidence: 89%
“…A further central question to solve is the influence of environmental or physiological cues (such as 3CBA metabolism in case of ICEclc) on the proportion of appearing tc cells. Such cues or changes in environmental conditions may unwillingly influence gene transfer rates within microbial communities [49][50][51] , and this may lead to enhanced adaptation of pathogenic isolates to antibiotic resistances carried by the ICE.…”
Section: Discussionmentioning
confidence: 99%
“…A further central question to solve is the influence of environmental or physiological cues (such as 3CBA metabolism in case of ICEclc) on the proportion of appearing tc cells. Such cues or changes in environmental conditions may unwillingly influence gene transfer rates within microbial communities [53][54][55], and this may lead to enhanced adaptation of pathogenic isolates to antibiotic resistances carried by the ICE.…”
Section: Plos Geneticsmentioning
confidence: 99%